A high-quality genome of Eragrostis curvula grass provides insights into Poaceae evolution and supports new strategies to enhance forage quality - Carballo, José (2019)
The Poaceae constitute a taxon of fowering plants (grasses) that cover almost all Earth?s inhabitable range and comprises some of the genera most commonly used for human and animal nutrition. Many of these crops have been sequenced, like rice, Brachypodium, maize and, more recently, wheat. Some important members are still considered orphan crops, lacking a sequenced genome, but having important traits that make them attractive for sequencing. Among these traits is apomixis, clonal reproduction by seeds, present in some members of the Poaceae like Eragrostis curvula. A de novo, high-quality genome assembly and annotation for E. curvula have been obtained by sequencing 602Mb of a diploid genotype using a strategy that combined long-read length sequencing with chromosome conformation capture. The scafold N50 for this assembly was 43.41Mb and the annotation yielded 56,469 genes. The availability of this genome assembly has allowed us to identify regions associated with forage quality and to develop strategies to sequence and assemble the complex tetraploid genotypes which harbor the apomixis control region(s). Understanding and subsequently manipulating the genetic drivers underlying apomixis could revolutionize agriculture.